GRAMMATICAL-SEMANTIC PROPERTIES OF VERB-PHRASE WITH “bae” and “kanai” in MINANGKABAUNESE - Jufrizal, NFN (Linguistik Indonesia, 2017)
The lexicons bae and kanai in Minangkabaunese can be combined with other verbs to form a serial verb construction, such as: bae lari ‘get running’, bae makan ‘get eating’, kanai tanyo ‘get asked’, and kanai bao ‘get brought’. The serial verb constructions bae or kanai + V in this local language bring about particular grammatical-semantic properties which need further analyses and discussion. This article, which is derived from a part of the results of a research entitled “Kemasan Makna Gramatikal dan Makna Sosial-Budaya Bahasa Minangkabau: Penyelidikan atas Tatamakna dan Fungsi Komunikatifnya”2 discusses the grammatical-semantic properties of verbal predicates in verb-phrase bae or kanai + V in the form of serial verb construction. The main question as the basis of analysis and discussion presented in this paper is ‘what are the grammatical-semantic properties of clause constructions with the predicate in verb-phrase bae or kanai + V in Minangkabaunese?’ The analysis and discussion are to explore and to explain the grammatical-typological and semantic properties of the serial verb constructions in Minangkabaunese. The data and information presented in this paper were obtained through a library and linguistic field research conducted in 2016. The analysis and discussion on the data are based on relevant theories of linguistic typology, especially the grammatical typology dealing with grammatical constructions and active-passive voice.